REACTIONS INDUCED BY ANTIPROTONS – A REVIEW - Rana, M. A.; Shahzad, M. I.; Manzoor, S.; Sher, G. (The Nucleus, 2020)
Antiproton interactions with target atoms, its annihilation with a proton or a neutron inside nuclei and decays of excited nuclei formed after antiproton annihilation in them are reviewed here briefly, but comprehensively. Various models describing interactions of antiprotons with matter are examined carefully. Experimental data of antiproton annihilation cross section with nucleons (protons and neutrons), pion emission following annihilation and their interaction with the nucleus, excitation energy of the nucleus and light particle emission for nuclei from 12C to 238U is compiled from the literature and analyzed. Moreover, data sets about antiproton-induced fission of nuclei from 209Bi to 238U and heavy quark pair production are also reviewed. Use of antiprotons for bioapplications is discussed. Results reviewed here make a picture of antiproton annihilation in target nuclei including essential details.